Vesico-Vaginal Fistula a leading cause of Traumatic Stress In sufferers - Ahmed, Sadaf; Noushad, Shamoon; Syed, Shershah; Ahmed, Faiza (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To evaluate psychological constraints among patients presenting with vesico-vaginal fistula (VVF). Methods: An Observational exploratory study was carried out to explore the experiences of women suffering from VVF. The study included 16 women hospitalized with the diagnosis of VVF at Kohi Goth Women's Hospital, Karachi, Pakistan. All patients presenting with VVF were administered a structured questionnaire followed by an in-depth interview while Sadaf Stress Scale was utilized for the evaluation of psychological condition. Results: The average age of patients was 25.4 years, range 24-30 years. A total of 5 patients were diagnosed with severe traumatic stress, only 1 patient was found in moderate level. While non to of the patients were unable to find proper mental health treatment due to poverty & illiteracy. Severity of traumatic stress was found greater in early years of the disease. All patients were affected by untrained Midwives. Conclusions: VVF is leading to traumatic stress, if not treated in early stages could lead to post traumatic stress disorder. The need to empower patients to timely access standard maternity and emergency obstetric care & mental health care is recommended.